At the Forefront, Looking Ahead Research-Based Answers to Contemporary Uncertainties of Management - Amir Sasson (Scandinavian University Press (Universitetsforlaget), 2018)
This book presents research-based answers to some of the uncertainties that managers, investors, employees and policymakers face. On its 75th anniversary, BI Norwegian Business School is undoubtedly a researchbased school at the forefront of global research. Its research groups contribute excellent, original research that is at the international forefront appearing in top international journals, while its graduates, more than those of any other school, populate CEO positions. Being at the forefront requires that we look ahead, not merely celebrate past successes. This book does exactly that. It covers three themes: 1. The digital organization, including algorithm-based decision making and management, digital labour, business models, corporate reputation and branding 2. The governance of corporations, with specific reference to state-owned and family-owned firms and their auditing 3. Decision-making, incentives and innovation, covering issues such as employee motivation and creativity, environmental R&D, political decision-making and customer experience